A conquista de direitos trabalhistas: lutas sociais dos assalariados rurais da cana-de-açúcar no agreste e brejo paraibano (1980-1987) - Costa, Lidineide Vieira da (2019)
The present dissertation analyzes the process of struggle for labor rights of rural sugarcane workers in Agreste and Brejo Paraibano between 1980 and 1987, seeking to understand the construction of a project aimed at the diffusion of labor rights in the activity. Sugar cane plantation of Paraíba, forged from the process of political awareness / training of workers and affirmation of legislation in workplaces and public spaces. In this understanding, it is presented the performance of social organizations with the category of sugarcane workers in the conformation of labor rights, such as some progressive segments of the Catholic Church, rural trade union movement and other representative bodies of the class, also paying attention to the approach of the Labor Judiciary. to the interior areas of Paraíba. From the problematic posed, from the perspective of the Social History and the Social History of Work, we sought to cast new perspectives on labor relations in the Paraiba sugarcane zone, as well as to foster meaningful discussions about the “worlds of work” and their nuances in the sugarcane fields. For the construction of the historical narrative, documents (reports, clipping material, correspondence, information, among others) were used from the collection of the Popular Education Service (SEDUP), news from the Paraíba newspaper A União and labor disputes of TRT-13 (Labor Regional Tribunal – 13th Region) archived at the Nucleus of Historical Documentation of the Humanities Center of Paraíba State University (NDH-CH / UEPB).